Identification of the metabolic protein ATP5MF as a potential therapeutic target of TNBC - Kaiyan Chen; Yingchun Wu; Linfeng Xu; Changyong Wang; Jinqiu Xue (Journal of Translational Medicine)
Abstract Background Triple-negative breast cancer (TNBC), a distinct subtype of breast cancer, is characterized by its high invasiveness, high metastatic potential, proneness to relapse, and poor prognosis. Effective treatment regimens for non-BRCA1/2 mutation TNBC are still lacking. As a result, there is a pressing clinical necessity to develop novel treatment approaches for non-BRCA1/2 mutation TNBC. Methods For this research, the scRNA data was obtained from the GEO database, while the transcriptome data was obtained from the TCGA and METABRIC databases. Quality control procedures were conducted on single-cell sequencing data. and then annotation and the Copycat algorithm were applied for anlysis. Employing the high dimensional weighted gene coexpression network analysis (hdWGCNA) method, we analyzed the tumor epithelial cells from non-BRCA1/2 mutation TNBC to identify the functional module genes. PPI analysis and survival analysis were further emplyed to identify the key gene. siRNA-NC and siRNA-ATP5MF were transfected into two MDA-MB-231 and BT-549 TNBC cell lines. Cell growth was determined by CCK8 assay, colony formation and migration assay. Electron microscopy was used to examine the structure of mitochondria in cells. JC-1 staining was used to measure the potential of the mitochondrial membrane. A tumor xenograft animal model was established by injecting TNBC cells into nude mice. The animal model was usded to evaluated in vivo tumor response aftering ATP5MF silencing. Results Using hdWGCNA, we have identified 136 genes in module 3. After PPI and survival analysis, we have identified ATP5MF as a potential therapeutic gene. High ATP5MF expression was associated with poor prognosis of non-BRCA1/2 mutation TNBC. The high expression of ATP5MF in TNBC tissues was evaluated using the TCGA database and IHC staining of clinical TNBC specimens. Silencing ATP5MF in two TNBC cell lines reduced the growth and colony formation of TNBC cells in vitro, and hindered the growth of TNBC xenografts in vivo. Additionally, ATP5MF knockdown impaired mitochondrial functions in TNBC cells. Conclusion In summary, the metabolic protein ATP5MF plays a crucial role in the non-BRCA1/2 mutation TNBC cells, making it a potential novel diagnostic and therapeutic oncotarget for non-BRCA1/2 mutation TNBC.